2022
DOI: 10.3390/antibiotics11020146
|View full text |Cite
|
Sign up to set email alerts
|

Thymus zygis Essential Oil: Phytochemical Characterization, Bioactivity Evaluation and Synergistic Effect with Antibiotics against Staphylococcus aureus

Abstract: Staphylococcus aureus is a nosocomial bacterium causing different infectious diseases, ranging from skin and soft-tissue infections to more serious and life-threatening infections such as sepsis, meningitis and endocarditis, which may be exacerbated by antibiotic resistance. Plant products may be seen as an alternative as antibacterial agents, namely, against S. aureus. Thus, the aim of this work was to characterize the chemical composition and evaluate the bioactive properties of the T. zygis essential oil (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…The antibiofilm activity of enriched honey was tested by assessing their ability to inhibit biofilm formation and disrupt pre-formed biofilms by S. aureus ATCC 25923, according to Coimbra et al (2022) [ 70 ]. For this purpose, S. aureus was initially grown in TSB broth overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The antibiofilm activity of enriched honey was tested by assessing their ability to inhibit biofilm formation and disrupt pre-formed biofilms by S. aureus ATCC 25923, according to Coimbra et al (2022) [ 70 ]. For this purpose, S. aureus was initially grown in TSB broth overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A 0.5 McFarland suspensions were made from bacterial cultures in sterile saline solution. Antimicrobial disks (Filtar Lab, 6 mm Ø) were impregnated with 10 µL each of a hydroethanolic extract or an aqueous infusion of P. avium leaves, stems, and flowers, following to the method previously described [ 23 ], with small modifications. Gentamycin was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…S. aureus is a common nosocomial bacterium that can cause different infections, from those on the skin and in soft tissue infections to those that are more serious and life-threatening, such as sepsis. 41 , 42 The TEM images showed that the CWSNs can adhere to the surfaces of S. aureus cells, which suggests that they may interact with some specific components on the bacterial surface. Bacteria cell walls contain peptidoglycan consisting of amino acid residues, which may coordinate to the metal ions in the CWSNs.…”
Section: Discussionmentioning
confidence: 99%